In silico and in vivo Evaluation of Antitumor Drugs against P. falciparum 3D7 Inhibit the Parasite Growth - Aatif, Mohammad; Farhan, Mohd; Muteeb, Ghazala (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Plasmodium falciparum (P. falciparum) is the most lethal parasite that affectsmalaria in humans. The drugs such as Etoposide, Novobiocin, Netropsin, Nogalamycin and Daunorubicin may be useful in treating such diseases. Here, molecular docking study predicts the novel drug candidate. Further, computational and in vivo of the pharmacokinetic properties also helps to predict the drug candidate. Materials and Methods: At first, we optimized five antitumor drugs Etoposide, Novobiocin, Netropsin, Nogalamycin and Daunorubicin then analyze the frontier molecular orbitals followed by molecular docking against the target protein {PF3D7_1441900 (transcription factor TFIIH complex subunit Tfb5, putative) P. falciparum (isolate 3D7)}. Pharmacokinetic properties calculated by using the ADMET 2.0. We used SYBR green dye assess anti-malarial drugs (Etoposide, Novobiocin, Netropsin, Nogalamycin and Daunorubicin) against the malaria parasite 3D7 based on the fluorescence assay. Results: Our calculations show that all the studied drugs Etoposide, Novobiocin, Netropsin, Nogalamycin and Daunorubicin can have an affinity with the Plasmodium falciparum (isolate 3D7)}. ADME computed permeability, distribution, and metabolism characteristics of the drugs. We found in our in vivo 7 in silico study that Novobiocin and etoposide are valuable and maximum inhibition of the parasite P. falciparum 3D7 strain growth in comparison to others. Conclusion: Our study concluded that Etoposide and Novobiocin could illustration the better affinity with the protein Plasmodium falciparum. The ADME analysis can be used for evaluating the pharmacokinetic properties. Novobiocin is possible inhibitor for malaria.
Keywords: Plasmodium falciparum; Drugs; FMO; DFT; Molecular Docking; ADME. Inhibition; Parasite growth